Estrategias didácticas para el desarrollo de la expresión corporal en la danza en los estudiantes de tercer nivel, con mención de profesores de educación básica del 2º a 7º año, nivel tecnológico, del Instituto Superior Pedagógico José Gabriel Vega Vetancourt, Santa Rosa – El Oro, periodo lectivo 2013. - Borja Cruz, Silvana Lupita (2014)
Education is a key factor of social development , so he is devoting great resources for effective improvement, and it is in this new millennium where increasingly higher changes required in the training of professionals . At present the study of aesthetic culture is important because it is one of the fields of theoretical and practical application and it is precisely within the scope of this activity which is more relevant when specific techniques are used as own dance , dance and body expression. The characterization of the teaching and learning of corporal expression in dance , revealed as a scientific problem , How to strengthen the body language in the dance students of the third level , with mention of teachers in basic education of the 2nd to 7th year , technological level, the pedagogical institute José Gabriel Vega Betancourt , Santa Rosa , El Oro, school year 2013?